The Application of FPGA in PWM Controlled Resonant Converter for an Ozone Generator - Mochammad Facta; Tole Sutikno; Zainal Salam (Institute of Advanced Engineering and Science, 2013)
Pulse Width Modulation (PWM) is a very common technique used in many different applications. The Conventional method its generation is the heart of the inverter system. This paper present methodology to generate Sinusoidal PWM (SPWM) signal for three-phase inverter based on EP20K200EFC484-2x Altera Field Programmable Gate Array (FPGA). Designing a PWM inverter drive using FPGA has several advantages, such as: it's quick, very modifiable, and very suitable for prototyping. In this paper, the PWM signal is used control switching action conducted by MOSFET as part of power electronics devices in resonant power converter which has 24 volt DC input voltage. As the result, by using resonant oscillation controlled by FPGA the high sinusoidal voltage until 1.0 kV peak-to peak has been generated in the load side.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.4316